Faktor-faktor Penentu Profitabilitas Bank Syariah di Indonesia (Management Analysis Journal, 2015)
This research aimed to determine the influence of third party funds (DPK), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), SWBI (Indonesian Wadiah Certificates Bank ) toward Return on Assets (ROA ) on Syariah Banks in Indonesia. The population in this study were all registered Syariah banking at Bank Indonesia, those are 11 Syariah Banks (BUS). The sampling technique used was purposive sampling criteria, which result were 4 Syariah banks. This study was using multiple linear regression analysis. Data used in this research were obtained from Bank Indonesia during the period of 2011 to 2013. Data analysis methods used in the study were multiple linear regression analysis, the classical assumption test, and test hypotheses. The result of the research show that the DPK, NPF, FDR, ROA and SWBI simultaneously affect the ROA. Data analysis methods used in the study were multiple linear regression analysis, the classical assumption test, and test hypotheses. The result of the research show that the DPK, NPF, FDR, ROA and SWBI simultaneously affect the ROA